2006
DOI: 10.1007/s11547-006-0005-8
|View full text |Cite
|
Sign up to set email alerts
|

Supraspinatus tendon US morphology in basketball players: correlation with main pathologic models of secondary impingement syndrome in young overhead athletes. Preliminary report

Abstract: Despite the study limitations, ultrasonography (US) is able to detect subacromial space narrowing in young overhead athletes as early shoulder impingement sign, according to the continuum impingement-instability pathologic model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 20 publications
0
48
0
Order By: Relevance
“…Prior studies using ultrasound to measure the AHD in individuals with RCD imaged the SAS over the middle 2,3 or anterior 10 aspect of the SAS space, or did not describe location 14 of the ultrasound probe. Findings from these ultrasound studies were generally consistent with those using MRI to image the SAS, 1,15,19 which depicted the AHD measure of the anterior to middle aspect of the SAS or described it as the smallest distance between the acromion and humerus regardless of location in the SAS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies using ultrasound to measure the AHD in individuals with RCD imaged the SAS over the middle 2,3 or anterior 10 aspect of the SAS space, or did not describe location 14 of the ultrasound probe. Findings from these ultrasound studies were generally consistent with those using MRI to image the SAS, 1,15,19 which depicted the AHD measure of the anterior to middle aspect of the SAS or described it as the smallest distance between the acromion and humerus regardless of location in the SAS.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,14,15,19 Studies using MRI reported a smaller AHD in patients with impingement syndrome as compared to healthy shoulders. 1,15,19 Studies using ultrasound imaging corroborate these findings with a smaller AHD in patients with RCD 3,14 and a smaller AHD with increased severity of the RCD.…”
mentioning
confidence: 99%
“…If the intensity of demand and time ratio is disproportionate the tendon undergoes disrepair. To further add to the debate, Girometti et al 2006, used ultrasound to…”
Section: Intrinsic Mechanisms Influencing the Subacromial Spacementioning
confidence: 99%
“…7 The acromiohumeral distance (AHD) is a twodimensional linear measurement of the subacromial space and a widely recognized marker for rotator cuff disease. 8 AHD measurement has been well established in previous studies with able-bodied individuals with healthy shoulders, [9][10][11] athletes, [12][13][14][15] patients with SIS, 16,17 patients with poststroke hemiplegia, 11 individuals with different stages of rotator cuff degeneration, 18 and patients with rotator cuff tear. 8 Ultrasonography has increasingly been used as an imaging modality for measuring the AHD because it is portable, radiation-free, and non-invasive.…”
Section: Introductionmentioning
confidence: 99%